Hadith and Ecological Harmony: A Contextual Interpretation of the Prohibition Against Cursing the Wind Amid the Global Environmental Crisis - Muhammad Genta Saputra (STKQ Al-Hikam Depok, 2025)
The global ecological crisis reflects a profound imbalance in the relationship between humanity and nature, which is no longer within a sacred and ethical framework. This phenomenon signifies a form of spiritual degradation in perceiving nature as a manifestation of divine creation. This study aims to examine the prophetic prohibition against cursing the wind through the lens of Islamic social ethics by analyzing relevant hadiths within the frameworks of hermeneutics and maqasid al-shariah. This study uses a qualitative approach based on library research and thematic content analysis to engage classical hadith texts, exegetical literature, and contemporary Islamic scholarship. The findings demonstrate that Islam articulates a framework of ecological ethics rooted in reverence, cosmic responsibility, and spiritual consciousness toward nature as a divine sign. These findings underscore the urgency of revitalizing Islamic ethical values as a normative critique of human-induced environmental degradation and as an ethical paradigm uniting faith, sustainability, and ecological civility.